2022
DOI: 10.3389/fonc.2022.990603
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of multiple diagnostic methods for lymph node metastases of papillary thyroid carcinoma: A systematic review and meta-analysis

Abstract: ObjectiveThis study compared the diagnostic value of various diagnostic methods for lymph node metastasis (LNM) of papillary thyroid carcinoma (PTC) through network meta-analysis.MethodsIn this experiment, databases such as CNKI, Wanfang, PubMed, and Web of Science were retrieved according to the Cochrane database, Prisma, and NMAP command manual. A meta-analysis was performed using STATA 15.0, and the value of the surface under the cumulative ranking curve (SUCRA) was used to determine the most effective diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…The total score of this patient is 353 and the risk rate of HVLNM was 91.6%. meta-analysis reported that US + Computed Tomography FNA cytology + FNA-thyroglobulin (FNA-Tg) showed good diagnostic performance (23). The limitations are that these methods are radiative or invasive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total score of this patient is 353 and the risk rate of HVLNM was 91.6%. meta-analysis reported that US + Computed Tomography FNA cytology + FNA-thyroglobulin (FNA-Tg) showed good diagnostic performance (23). The limitations are that these methods are radiative or invasive.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the diagnostic efficacy was unsatisfactory, with a pooled sensitivity between 0.31 and 0.35 for detecting involved lymph nodes in the central neck ( 22 ). Another meta-analysis reported that US + Computed Tomography and FNA cytology + FNA-thyroglobulin (FNA-Tg) showed good diagnostic performance ( 23 ). The limitations are that these methods are radiative or invasive.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the methodological quality of studies was appraised using the Cochrane Handbook's risk-of-bias assessment tool (RevMan v.5.3.5, The Cochrane Collaboration) ( 20 ), covering six aspects (selection, performance bias, detection, attrition, reporting bias and other bias), which were categorized as ‘yes’, ‘no’ or ‘unclear’ to indicate the level of bias.…”
Section: Methodsmentioning
confidence: 99%
“…A recently published meta-analysis of 38 articles with 6,285 patients compared 12 modalities, namely, US, computed tomography (CT), US + CT, contrast-enhanced US (CEUS), magnetic resonance diffusion tensor imaging (MRI), F-18 fluorodeoxyglucose positron emission tomography/CT (PET/CT), 131I whole-body (IWBC), US + CEU, strain elastography (SE-US), fine-needle aspiration thyroglobulin (FNA-Tg), US-guided fine-needle aspiration cytology (FNAC), and FNAC-FNA-Tg. The results showed that the sensitivity was highest for US + CT, and the specificity was highest for FNAC (25). Research has been directed to evaluate the role of contrastenhanced CT (CECT) in assessing neck nodes (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%